Late Roman Villas and Cognitive Science. Issue 1 (15th July 2019) - Stephenson, John
Abstract : Without the benefit of cognitive or evolutionary theory, late Roman villa patrons and designers intuited their way toward houses that engaged and strongly affected the emotions of inhabitants and visitor participants. Through the lens of their unique cultural moment, they discovered and deployed strategies that respond to certain innate and universal human needs. These were the aspects of a formal language of design that arose from a competitive 'architectural arms race' among a newly minted elite in the era of the late empire, which left a heritage that echoes through the history of architecture. Through the application of methods in cognitive science we can recover some of those strategies and understand their effects with a new specificity. Cognitive science confirms, continues, and elucidates earlier discoveries in phenomenology and psychology, placing the embodied and active human agent into the center of the experience of ancient architecture.